Taxonomic revision of the Heligmonellidae (Skrjabin & Schikhobalova, 1952 tribe) Durette-Desset & Chabaud, 1977 (Nematoda) parasitic in arvicoline rodents "Eothenomys" (sensu lato) (Cricetidae) from Japan and Thailand. - Durette-Desset, Marie-Claude (2019)
We discuss the systematic position of five species of the Heligmonellidae (Skrjabin & Schikhobalova, 1952 tribe) Durette-Desset & Chabaud, 1977 described in arvicoline rodents “Eothenomys” (sensu lato) from Japan and Thailand, classified up to now in the genera Yatinema Asakawa & Ohbayashi, 1986, Carolinensis (Travassos, 1937), Morganiella Travassos, 1937 and Neoheligmonella Durette-Desset, 1971. The species are analysed, rediagnosed and their systematic position reviewed. A new generic arrangement is proposed mainly based on characters of the synlophe such as: the presence or absence of a careen; the relative size of the ridges of the careen with respect to the right ridge; the relative sizes of the left and right ridge; the size and position of ridge 1’; the presence or absence of gradients in ridge size; and the number of ridges. The taxa analysed are rearranged in three genera and six species, of which two genera and three species are new. The new classification proposed includes: Yatinema (sensu stricto) with Yatinema japonicum Asakawa & Ohbayashi, 1986 (type-species) and Y. niigatae n. sp. (syn. Y. japonicum sensu Asakawa & Ohbayashi, 1986 pro parte); Asakawanema n. g. with Asakawanema siamense n. comb. (syn. Yatinema siamensis Asakawa, Kamiya & Ohbayashi. 1986) as the type- and only species; and Fukumotonema n. g. with Fukumotonema orientale n. comb. (syn. Neoheligmonella orientalis Asakawa, Kamiya & Ohbayashi. 1986) (type-species), Fukumotonema deborahae n. sp. (syn. Yatinema japonicum sensu Asakawa, 1989 nec Asakawa & Ohbayashi. 1986), and Fukumotonema myodesi n. sp. (syn. Morganiella cricetuli sensu Asakawa et al., 1989 nec Yin & Zhang, 1981). Carolinensis eothenomysi Asakawa, Kamiya & Ohbayashi, 1986 and Morganiella cricetuli Yin & Zhang, 1981 are considered Nippostrongylinae incertae sedis. A key to the genera and species is provided.